21.9k views
5 votes
If f(x)=x-1/x g(x)=x-1 and h(x)=x+1 what is (g•h•f)(x)

2 Answers

1 vote

Answer:

( f o f )(x) = f ( f (x))

= f (2x + 3)

= 2( ) + 3 ... setting up to insert the input

= 2(2x + 3) + 3

= 4x + 6 + 3

= 4x + 9Step-by-step

Step-by-step explanation:

User Nander Speerstra
by
4.7k points
5 votes

Answer:

x - 1/x, which is also f(x)

Step-by-step explanation:

hf(x) = x - 1/x + 1

hf(x) = x + 1 - 1/x

ghf(x) = x + 1 - 1/x - 1 = x - 1/x = f(x)

User Sampath Janardhan
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.